2013
DOI: 10.1007/s12160-012-9431-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education and Student Activity: Evaluating Implementation of a New Policy in Los Angeles Public Schools

Abstract: Background California law has standards for physical education (PE) instruction in K-12 public schools; audits found that the Los Angeles Unified School District did not enforce the standards. In 2009, the district adopted a PE policy to comply with these standards. Purpose This study aimed to evaluate the outcomes of the PE policy in district schools. Methods PE class observations were conducted using the System for Observing Fitness Instruction Time in the 2010-2011 and 2011-2012 school years in an income-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
(24 reference statements)
1
29
0
Order By: Relevance
“…12 This finding is consistent with other direct observation studies using the original SOFIT tool, although these studies have found percents of MVPA ranging from 38-46%. 20,21,24 The proportion of lesson time lost to transition in this study (31.8%) was similar to other studies conducted in middle school PE classes, which found 19-36% of lost instructional time. 23,24,29,30 Thus, only an average of 68% of class time was spent engaged in content related to PE in this sample.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…12 This finding is consistent with other direct observation studies using the original SOFIT tool, although these studies have found percents of MVPA ranging from 38-46%. 20,21,24 The proportion of lesson time lost to transition in this study (31.8%) was similar to other studies conducted in middle school PE classes, which found 19-36% of lost instructional time. 23,24,29,30 Thus, only an average of 68% of class time was spent engaged in content related to PE in this sample.…”
Section: Discussionsupporting
confidence: 88%
“…20 As in the original SOFIT protocol, 31 four students in each class were observed on a rotating basis every 10 seconds over the duration of the class. Students were chosen at the beginning of each class to be roughly representative of the class in terms of gender and overweight status—two factors known to influence physical activity intensity and duration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all of the studies were cross-sectional and none were longitudinal. The majority of the studies focused on school-level implementation of state and/or district level policies [3846], followed by studies of the relationship between the policies and student PA [•41, •47], or youth obesity [48, 49]. …”
Section: Resultsmentioning
confidence: 99%
“…Nongovernmental organizations can also play a role in protecting the rights of communities through civil rights laws. In Los Angeles, a multidisciplinary coalition's assessment of the discriminatory impact of physical education requirements, a state mandate, and variation in resources (teachers and facilities) in schools with higher Latino and minority attendees resulted in changes in policies and practice (37,61). These communities are considering how best to use law and policy to support their populations, to advance health, and to eliminate inequities.…”
Section: Promising Efforts To Use Law and Policy To Address Health Eqmentioning
confidence: 99%